Analisis Perspektif Ulama, Psikolog, dan Mahasiswa Mengenai Kurangnya Iman Seseorang yang Berdampak pada Kesehatan Mental - Sekar Ashfiya Prabeus; Dewi Fadiyah Hadinah; Alia Nurul Faadiyah; Naila Adinda Rahmanisa; Achmad Faqihuddin (Yayasan Al-Afif, 2025)
Humans are creatures of God who are not immune to mental health diseases influenced by their environment. This research explores community views, particularly students, scholars, and psychologists, in assessing mental health. The analysis method used is qualitative, involving interviews with students who have experienced mental disorders and Literature Study and Review (LSR) to examine scholars' and psychologists' perspectives. The results show that scholars believe strong faith helps individuals live with gratitude, while weak faith makes them more prone to stress and depression. An Islamic psychologist stated that individuals with strong faith handle challenges calmly, whereas a lack of faith may lead to a spiritual void affecting mental health. Students agree that faith impacts mental health but emphasize that those experiencing mental issues should not be judged or assumed to lack faith or devotion.